2000
DOI: 10.1002/(sici)1097-4547(20000215)59:4<477::aid-jnr2>3.0.co;2-j
|View full text |Cite
|
Sign up to set email alerts
|

Oligodendrocytes and the control of myelination in vivo: new insights from the rat anterior medullary velum

Abstract: The rat anterior medullary velum (AMV) is representative of the brain and spinal cord, overall, and provides an almost two-dimensional preparation for investigating axon-glial interactions in vivo. Here, we review some of our findings on axon-oligodendrocyte unit relations in our adult, development, and injury paradigms: (1) adult oligodendrocytes are phenotypically heterogeneous, conforming to Del Rio Hortega's types I-IV, whereby differences in oligodendrocyte morphology, metabolism, myelin sheath radial and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
46
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 95 publications
(49 citation statements)
references
References 99 publications
3
46
0
Order By: Relevance
“…We hypothesize that only the PLPexpressing population may become myelinating oligodendrocytes. The other population may differentiate to become the NG2-positive cells found in adult brain, which have been proposed to function in an independent neuromodulatory role in the CNS (Bergles et al, 2000), because they contact nodes of Ranvier (Butt and Berry, 2000) and receive synaptic signals from axons (Bergles et al, 2000).…”
Section: Abstract: Oligodendroglia; Myelin; Progenitor Cells; Enhancmentioning
confidence: 99%
See 2 more Smart Citations
“…We hypothesize that only the PLPexpressing population may become myelinating oligodendrocytes. The other population may differentiate to become the NG2-positive cells found in adult brain, which have been proposed to function in an independent neuromodulatory role in the CNS (Bergles et al, 2000), because they contact nodes of Ranvier (Butt and Berry, 2000) and receive synaptic signals from axons (Bergles et al, 2000).…”
Section: Abstract: Oligodendroglia; Myelin; Progenitor Cells; Enhancmentioning
confidence: 99%
“…On the other hand, other important functions for these adult NG2-positive cells have been proposed that are quite distinct from a role as oligodendrocyte progenitors. Adult NG2-positive cells display a different morphology relative to their younger counterparts (Nishiyama et al, 1999), extending processes along axons to form discrete contacts with axolemma at nodes of Ranvier, perhaps suggesting a role for these cells relating to nodal function (Butt and Berry, 2000). It has also been proposed that adult NG2-positive cells may regulate synaptic growth and plasticity by glutamate signaling at the synapse (Bergles et al, 2000) or that they represent a population of Intensity of fluorescence increased as the cells became obviously myelinating cells, although cell density did not increase.…”
Section: Plp Promoter Activity In Ng2-positive Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…During development, oligodendrocytes first send multiple filopodia that contact and ensheath axons (Butt and Berry, 2000). After this initial loose ensheathment, non-ensheathing processes are removed and spiral wrapping of the axon commences, eventually forming the compact myelin.…”
Section: Introductionmentioning
confidence: 99%
“…In order to avoid these potential problems, some researchers directly transplanted OPCs into the injury site instead of ESCs and observed enhanced remyelination and recovery of motor function [22]. Since studies have reported that astroglial scar is correlated with the failure of remyelination [23,24], it suggested transplantation of OPCs at the early post-injury period after SCI. However, at the acute phase of injury, macrophages infiltrating from the blood and constitutive microglia are activated and may be toxic to the OPCs.…”
Section: Discussionmentioning
confidence: 99%